ANALYSIS OF THE EFFECTIVENESS OF INDIRECT SPINAL CANAL DECOMPRESSION IN THE TREATMENT OF BURST FRACTURES AT THE THORACOLUMBAR JUNCTION - Nekhlopochyn, Oleksii; Verbov, Vadim; Cheshuk, Ievgen; Vorodi, Milan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Indirect decompression of the spinal canal through ligamentotaxis is one of the methods for remodeling the spinal canal in traumatic stenosis. Objective: To evaluate the effectiveness of indirect decompression of the spinal canal for different morphological types of burst fractures of vertebral bodies at the thoracolumbar junction. Methods. A preoperative and postoperative analysis of computed tomography scans was performed on 59 patients who were treated at the«Romodanov Neurosurgery Institute, National Academy of Medical Sciences of Ukraine» for burst fractures at the thoracolumbar junction. The criterion for the effectiveness of indirect decompression was the area of the spinal canal, measured at the level of injury in the zone of maximum compression. The grading of burst fractures was performed using the classification by F. Magerl et al. (1994). Results. In the preoperative period, the median degree of stenosis in the group of patients was 43.47 % (95 % confidence interval (CI): 37.53–46.22 %). For damage type A3.1, it was 36.9 % (95 % CI: 28.1‒40.5 %), for type A3.2 — 46.1 % (95 % CI: 32.1‒54.5 %), and for type A3.3 — 47.6 % (95 % CI: 37.5‒56.5 %). After surgical treatment, the degree of stenosis decreased by 20.14 % (95 % CI: 15.93‒21.56 %). For type A3.1, the effectiveness was 20.1 % (95 % CI: 9.5‒22.7 %), for type A3.2 — 15.2 % (95 % CI: 7.51‒17.3 %), and for type A3.3 — 21.7 % (95 % CI: 20.8‒26.4 %). The difference between types A3.2 and A3.3 was statistically significant (p = 0.0018). It was found that indirect decompression is most effective with higher degrees of stenosis. For Grade I by D. Wolter (1988), the canalexpansion achieved was 7.07 % (95 % CI: 5.69‒8.65 %), for Grade II — 21.6 % (95 % CI: 20.4‒22.7 %), and for Grade III — 30.3 % (95 % CI: 27.0‒33.6 %). Conclusions. Closed remodeling of the spinal canal with transpedicular fixation and the effect of ligamentotaxis is an effective method for correcting traumatic spinal canal stenosis at the thoracolumbar junction. The effectiveness of the technique is determined by many factors, including the type of burst fracture, the initial degree of stenosis, and the level of injury.